Waterproofing spray-associated pneumonitis review: Comparison with acute eosinophilic pneumonia and hypersensitivity pneumonitis. Issue 10 (12th March 2021) - Shimoda, Masafumi; Tanaka, Yoshiaki; Fujiwara, Keiji; Furuuchi, Koji; Osawa, Takeshi; Morimoto, Kozo; Yano, Ryozo; Kokutou, Hiroyuki; Yoshimori, Kozo; Ohta, Ken
Abstract : Abstract: Waterproofing spray-associated pneumonitis (WAP) proceeds to acute respiratory failure and is characterized by diffuse bilateral ground-glass opacities on computed tomography; however, the detailed characteristics of WAP are unknown. Therefore, this study identified the characteristics of WAP from comparisons with those of acute eosinophilic pneumonia (AEP) and hypersensitivity pneumonitis (HP), which show similar features to WAP. Adult patients with WAP, AEP, and HP treated in Fukujuji Hospital from 1990 to 2018 were retrospectively enrolled. Furthermore, data from patients with WAP were collected from publications in PubMed and the Japan Medical Abstracts Society and combined with data from our patients. Thirty-three patients with WAP, eleven patients with AEP, and thirty patients with HP were reviewed. Regarding age, sex, smoking habit, and laboratory findings (white blood cell count, C-reactive protein level, and serum Krebs von den Lungen-6 level), WAP and AEP were not significantly different, while WAP and HP were significantly different. The duration from symptom appearance to hospital visit was shorter in patients with WAP (median 1 day) than in patients with AEP (median 3 days, P  = .006) or HP (median 30 days, P  < .001). The dominant cells in the bronchoalveolar lavage fluid of patients with WAP, AEP, and HP were different (macrophages, eosinophils, and lymphocytes, respectively). The characteristic features of WAP were rapid disease progression and macrophage dominance in the bronchoalveolar lavage fluid, and these characteristics can be used to distinguish among WAP, AEP, and HP. Abstract : Supplemental Digital Content is available in the text